The usage of enabling technologies of industry 4.0: blockchain in the insurance sector - Malyzhenkov P. V. (Socio-Economic Processes of Modern Society, 2023)
the growth in the number of online payments and transactions in financial markets is exacerbating problems of personal data safety and identity security, which increases the demand for data encryption technologies. While demanding safer and better financial services, not all users are willing to pay high transaction costs. Distributed ledger technology can reduce costs and also increase the reliability of any type of transaction. In the future, such technology can completely transform the financial sector and significantly reduce the role of intermediaries
Keywords: страхование; блокчейн; blockchain; использование технологий; страховой сектор; use of technology; Insurance sector; insurance